Impact of withdrawal of the analgesic Co-proxamol on nonfatal self-poisoning in the UK. - Hawton, K; Bergen, H; Waters, K; Murphy, E; Cooper, J; Kapur, N (2011)
BACKGROUND: In early 2005 the UK Committee on Safety of Medicines (CSM) announced gradual withdrawal of the analgesic co-proxamol because of its adverse benefit/safety ratio, especially its use for intentional and accidental fatal poisoning. Prescriptions of co-proxamol were reduced in the 3-year withdrawal phase (2005 to 2007) following the CSM announcement. AIMS: To assess the impact of the CSM announcement in January 2005 to withdraw co-proxamol on nonfatal self-poisoning with co-proxamol and other analgesics. METHODS: Interrupted time series analysis of general hospital presentations for nonfatal self-poisoning (five hospitals in three centers in England), comparing the 3-year withdrawal period 2005-2007 with 2000-2004. RESULTS: A marked reduction in the number of episodes of nonfatal self-poisoning episodes involving co-proxamol was found following the CSM announcement (an estimated 62% over the period 2005 to 2007 compared to 2000 to 2004). There was no evidence of an increase in nonfatal self-poisoning episodes involving other analgesics (co-codamol, codeine, co-dydramol, dihydrocodeine, and tramadol) in relation to the CSM announcement over the same period, nor a change in the number of all episodes of self-poisoning. LIMITATIONS: Data were from three centers only. CONCLUSIONS: The impact of the policy appears to have reduced nonfatal self-poisoning with co-proxamol without significant substitution with other analgesics. This finding is in keeping with that for suicide.